Analisis Determinan Efisiensi Perbankan di Indonesia - Halim Azhar; Yeniwati Yeniwati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This study aims to determine the extent of the influence of bank size (total assets), capital adequacy (CAR) and credit risk (NPL) on banking efficiency in Indonesia. Banking efficiency in this study uses the BOPO indicator. This research is classified into descriptive and inductive research. The data used in this study is secondary data in the form of panel data on 27 conventional commercial banks in Indonesia from 2010 to 2019 obtained from the Financial Services Authority (OJK). This study uses a panel regression analysis method. The results of the study using the Fixed Effect Model (FEM) show that: (1) Bank size (total assets) has a negative and insignificant effect on bank efficiency in Indonesia, (2) Capital adequacy (car) has a negative and insignificant effect on bank efficiency. negative and insignificant to bank efficiency in Indonesia, (3) Credit risk (NPL) has a negative and significant effect on bank efficiency in Indonesia. (4) Bank size (total assets), Capital adequacy (car) and credit risk together significant effect on banking efficiency in Indonesia.